Real World Experience of Daratumumab: Evaluating Lymphopenia and Adverse Events in Multiple Myeloma Patients - Cottini, Francesca; Huang, Ying; Williams, Nita; Bumma, Naresh; Khan, Abdullah M.; Chaudhry, Maria; Devarakonda, Srinivas; Efebera, Yvonne A.; Benson, Don M.; Rosko, Ashley E. (Frontiers in Oncology, 2021)
Multiple myeloma (MM) is an incurable disease with a limited life expectancy of five years from diagnosis. Uncontrolled disease or infections are the main causes of mortality. Daratumumab, a monoclonal antibody against CD38, is approved to treat patients with MM. Its target, CD38, is expressed not only on MM cells but also on common lymphoid precursors and subsets of normal lymphocytes. Daratumumab-induced lymphopenia is common, but its clinical significance is understudied. In this study, we report the baseline characteristics, rates of severe lymphopenia, infections, and clinical trajectory of multiple myeloma patients (n=100) treated with daratumumab-based regimens at the Ohio State University Comprehensive Cancer Center. We discover high rates of infections, hospital utilization, and severe lymphopenia and identify risks factors for severe lymphopenia, such as low pretreatment absolute lymphocyte count (ALC) values. Severe lymphopenia persists in 23% of patients, resulting in worst survival outcomes. Our data underline the importance of monitoring ALC and consider future use of prophylactic measures or alternative regimens in subsets of MM patients.